Peran Guru Kelas Dalam Menumbuhkan Rasa Percaya Diri Pada Siswa Kelas IV SD Negeri 24 Palembang - Daniarsi, Rani; Ferdiansyah, M; Laksana, Robert Budi (Institut Teknologi Pendidikan Indonesia, 2022)
The role of the teacher in fostering self-confidence in students is very important. Teachers are required to be more creative in using and adapting the teacher's role. This study aims to determine the role of classroom teachers in fostering self-confidence in grade IV.C students at SD Negeri 24 Palembang. The research method used in this research is the descriptive qualitative method. The descriptive method is a method with data collected in the form of words or sentences or pictures that have meaning with real understanding. Data collection techniques used are observation, interviews, and documentation. Based on the results of research and discussion, it can be concluded that the teacher's role in fostering selfconfidence in fourth-grade students is that the teacher acts as (1) mediator and facilitator; (2) motivator, and; (3) class manager. It can be seen how the learning that has been done by the IV.C homeroom teacher in fostering self-confidence in the fourth-grade students.